1989
DOI: 10.1159/000195734
|View full text |Cite
|
Sign up to set email alerts
|

Value of Two-Dimensional Echocardiography in the Identification of Pulmonary Hypertension in Chronic Obstructive Lung Disease

Abstract: Thirty-three patients suffering from chronic obstructive lung disease (COLD) were submitted to right heart two-dimensional echocardiographic (2D-ECHO) and hemodynamic study. By the subcostal approach, the right ventricle outflow tract including the pulmonary vessels was visualized in 85% of the patients. Most parameters measured on the right ventricle and pulmonary vessels were significantly higher than those recorded in the healthy control group. Very significant correlations were observed between the mean pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…There was good correlation between echocardiographic parameters, hemodynamics and pulmonary function parameters. 9 the authors concluded that echocardiography may be a useful technique in the non-invasive assessment of pulmonary hypertension on right heart in COPD.…”
Section: Review Of Literaturementioning
confidence: 99%
“…There was good correlation between echocardiographic parameters, hemodynamics and pulmonary function parameters. 9 the authors concluded that echocardiography may be a useful technique in the non-invasive assessment of pulmonary hypertension on right heart in COPD.…”
Section: Review Of Literaturementioning
confidence: 99%